1991
DOI: 10.1084/jem.173.5.1099
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T lymphocyte granules are secretory lysosomes, containing both perforin and granzymes.

Abstract: SummaryCytotoxic T lymphocytes (CTL) contain granules that are exocytosed during specific interaction with target cells (TC). In this process, the granule contents, including the lethal protein perforin, as well as granzymes, a family of serine esterases, are delivered to the TC . Information regarding the routing of these proteins towards the granule and their exact localization within the granule is of primary importance to resolve the mechanism of granule-mediated TC killing . In this study, the subcellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
439
0
7

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 613 publications
(466 citation statements)
references
References 50 publications
14
439
0
7
Order By: Relevance
“…We determined that MIA protein secretion is a Ca 2+ -regulated process, similar to the previously described secretion of many other specialized exocytic vesicles such as azurophile granules in neutrophils [44], specific granules in mast cells [45] and lytic granules in cytotoxic Tlymphocytes [46,47]. The most thoroughly characterized Ca 2+ -triggered exocytosis is the release of neurotransmitters into the synaptic space [48].…”
Section: Mia Protein Secretion Is a Ca 2+ -Regulated Process And Is Dmentioning
confidence: 76%
“…We determined that MIA protein secretion is a Ca 2+ -regulated process, similar to the previously described secretion of many other specialized exocytic vesicles such as azurophile granules in neutrophils [44], specific granules in mast cells [45] and lytic granules in cytotoxic Tlymphocytes [46,47]. The most thoroughly characterized Ca 2+ -triggered exocytosis is the release of neurotransmitters into the synaptic space [48].…”
Section: Mia Protein Secretion Is a Ca 2+ -Regulated Process And Is Dmentioning
confidence: 76%
“…Degranulation can be detected by exposure of the lysosomal-membrane-associated glycoproteins, CD107a, CD107b, and CD63, on the lymphocyte surface (53). These molecules are found in the granule-membrane inner surface and are exposed onto the lymphocyte surface through degranulation (53)(54)(55). It has been suggested that lysosomalmembrane-associated glycoproteins and the soluble protein cathepsin-B play an important role in avoiding lymphocyte self-destruction.…”
Section: Granule-dependent Exocytosis Pathwaymentioning
confidence: 99%
“…Perforin is found in a soluble monomer shape within granules and, after the cytotoxic-cell/target-cell junction, perforin is released by exocytosis (54). Once it is anchored, perforin begins the polymerization in the presence of Ca 2+ to form cylindrical pores with an internal diameter of 5 to 20 nm (63,65,66).…”
Section: Volume 6 Number 1 February 2009mentioning
confidence: 99%
“…Prominent in the CTL cytoplasm are secretory granules that contain a spectrum of cytotoxic molecules including perforin (Pfp) 4 and a group of serine proteases (11) called granzymes (granule enzymes; Gzm). After CTL engagement via TCR-mediated recognition of viral peptides (p) complexed with self-class I MHC glycoproteins (pMHCI), the granules move toward the CTL target interface where secretion of the cytotoxic contents results in apoptotic cell death.…”
mentioning
confidence: 99%